Tajne organizacje harcerskie w Polsce w latach 1944–1956 - Rzeczkowska, Ewa (Pamięć i Sprawiedliwość, 2011)
Secret scouting organizations are considered to have been an important element of the Polish independence underground in post-war Poland. During the period 1944–1956, at least 122 secret youth organizations were formed in Poland, whichideologically and structurally referred to scouting movement. Being a response to current political and social situation in Poland, they were born spontaneously. Those secret groups used to resort to various forms of defiance against the communistsystem among which the most important one was a propaganda activity similar to “minor-sabotage” operations carried out by the Szare Szeregi [the Grey Ranks]. The scouts painted anti-communist and anti-Soviet slogans on the walls, distributedillegal papers, newspapers and leaflets. Some of the organizations carried out various sabotage operations, such as: the disarming People’s Army of Poland [Ludowe Wojsko Polskie, LWP] and Red Army soldiers as well as MO [Milicja Obywatelska, the Citizens’ Militia] and UB [Urząd Bezpieczeństwa, the SecurityOffice] functionaries, the trains’ derailing, the banks, post offices and shops raiding. Young people, basing on the pre-war patterns, conducted a typical scouting activity. They organized scout camps and bivouacs, gained successive scout degrees and skills. A scout conspiracy was rather short-term – from a few to several months, nevertheless there were particular organizations being active for years. However, sometimes a responsibility for “slip-ups” fell on conspirators who carried out their actions without following necessary precautions, like a carbon paper already used to copy the organization statute or a leaflet, carelessly thrown out to a dustbin. Polish underground groups were worked out by the developed secret collaborators network of the Security Office [Urząd Bezpieczeństwa, UB]. Once UB managed to track down even one of the conspirators it meant the end of functioning of the whole group. The arrestment of one of the scouts was shortly followed by another. Detained young people were subjected to an immediate enquiry and put under psychical and brutal physical pressure. Statements taken in that way, provided afirm basis for bringing the case to military court. Every effort was made to give the trial propagandist character and thus its particular elements were carefully directed – starting from reading off an indictment act to pronouncing a sentence. What is more, the young people’s trials must have been reported in media. In consequence of judicial proceedings, harsh sentences were carried out completely disproportionate to the committed “offences”. People were sentenced to at least a few years in prison and courts did not hesitate to impose substantial punishments.